Surfing through the GFC: Systemic Risk in Australia1. Issue 300 (21st December 2016) - Dungey, Mardi; Matei, Marius; Luciani, Matteo; Veredas, David
Abstract : We provide empirical evidence on the degree of systemic risk in Australia before, during and after the global financial crisis. We calculate a daily index of systemic risk from 2004 to 2013 in order to understand how real economy firms influence the outcomes for the rest of the economy. This is done via a mapping of the interconnectedness of the financial and non‐financial sectors. The financial sector is in general home to the most consistently systemically risky firms in the economy. The materials sector occasionally becomes as systemically risky as the financial sector, reflecting the importance of understanding these linkages.